Bidrohee Bangla: memorial for the rebels of Bengal, Karnaphulli riverbank, Chittagong - Rubaiyat-Ur-Rahman (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2012.